An overview of the optical properties and applications of black phosphorus. Issue 6 (6th January 2020) - Chen, Xing; Ponraj, Joice Sophia; Fan, Dianyuan; Zhang, Han
Abstract : Since the year 2014, when scientists first obtained black phosphorus using a sticky tape to peel the layers off, it has attracted tremendous interest as a novel two-dimensional material. Abstract : Since the year 2014, when scientists first obtained black phosphorus using a sticky tape to peel the layers off, it has attracted tremendous interest as a novel two-dimensional material. After it was successfully produced, its outstanding optical properties have been unveiled. Various applications based on these properties have been reported. This study mainly reviews the unique optical properties and potential applications of black phosphorus. The optical performances of black phosphorus mainly include linear optical properties and nonlinear optical properties. Some examples include the anisotropic optical response, saturable absorption effect and Kerr effect. The researchers found that the nonlinear saturable absorption coefficients of black phosphorus are better than that of MoS2 and WS2 from the visible region to the near-infrared region. Compared with graphene, black phosphorus has a better nonlinear saturable absorption performance. After passivation or surface modification, black phosphorus is stable when exposed to oxygen and water. Herein, black phosphorus has the potential to be used in detector/sensors, solar energy harvesting, photocatalysts, optical saturable absorbers in ultrafast lasers, all optical switches, optical modulation, nanomedicine and some others in the near future.